Aerospace materials [electronic resource] / edited by Brian Cantor, Hazel Assender and Patrick Grant. - Cantor, Brian (Bristol ; Philadelphia : Institute of Physics, c2001., 2018)
1 online resource (xii, 312 p.) : ill.